Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1007/s10557-018-6811-0
|View full text |Cite|
|
Sign up to set email alerts
|

Exposure to Stress-Dose Steroids and Lethal Septic Shock After In-Hospital Cardiac Arrest: Individual Patient Data Reanalysis of Two Prior Randomized Clinical Trials that Evaluated the Vasopressin–Steroids–Epinephrine Combination Versus Epinephrine Alone

Abstract: In this reanalysis, exposure to stress-dose steroids (primarily in the context of a combined VSE intervention) was associated with lower risk of postresuscitation lethal septic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…234,235 Post hoc analysis of these trials found increased benefit of steroids in patients with septic shock. 236 A blinded RCT of 50 patients after CA found no difference between the hydrocortisone and placebo groups in time to shock reversal, shock reversal, good neurological outcome, or survival to discharge. 237…”
Section: Corticosteroidsmentioning
confidence: 99%
“…234,235 Post hoc analysis of these trials found increased benefit of steroids in patients with septic shock. 236 A blinded RCT of 50 patients after CA found no difference between the hydrocortisone and placebo groups in time to shock reversal, shock reversal, good neurological outcome, or survival to discharge. 237…”
Section: Corticosteroidsmentioning
confidence: 99%
“…Both trials found that the vasopressin-epinephrine-steroid group did better than the comparator group [ 233 , 234 ]. Post hoc analysis of these trials found increased benefit of steroids in patients with septic shock [ 235 ]. A blinded RCT of 50 patients after CA found no difference between the hydrocortisone and placebo groups in time to shock reversal, shock reversal, good neurological outcome, or survival to discharge [ 236 ].…”
Section: Endocrine and Fluids Management In The Icumentioning
confidence: 99%
“…In the context of the vasopressin–steroids–epinephrine (VSE) protocol, early post-ROSC, stress dose steroids may contribute to hemodynamic stabilization, especially in patients requiring high doses of vasopressors (e.g., norepinephrine equivalent ≥ 0.25 μg kg −1 min −1 ) and who have multiple organ failure [ 136 , 137 ]. In addition, a re-analysis of combined data from the two randomized VSE trials reported that exposure to stress dose steroids was associated with a lower risk of post-resuscitation lethal septic shock [ 138 ]. Nevertheless, a more recent, two-center, randomized trial of stress dose steroids (alone) vs. placebo did not confirm any steroid-associated physiological benefit [ 139 ].…”
Section: Circulatory Managementmentioning
confidence: 99%
“…Perhaps the most important to recognize is the patient who is fluid responsive but not fluid tolerant because this patient will be harmed by a fluid responsiveness-based strategy [ 138 ]. As multiple factors can impact the ability of different organs and compartments to accommodate fluids and maintain their function, and different patient phenotypes exist, frequent multimodal and comprehensive clinical assessments of fluid responsiveness and tolerance are necessary.…”
Section: Circulatory Managementmentioning
confidence: 99%